On the role of solution-processed bathocuproine in high-efficiency inverted perovskite solar cells. (April 2021) - Chiang, Shou-En; Chandel, Anjali; Thakur, Diksha; Chen, Yan-Ta; Lin, Pei-Chen; Wu, Jia-Ren; Cai, Kun-Bin; Kassou, Said; Yeh, Jui-Ming; Yuan, Chi-Tsu; Shen, Ji-Lin; Chang, Sheng Hsiung
Graphical abstract: Highlights: Solution-processed BCP small molecules can penetrate into the PCBM thin film and PCBM/MAPbI3 interface. The electron transportation in the PCBM thin film can be improved by doping BCP small molecules. The interfacial MA cations can be passivated by the penetrating BCP small molecules. A high PCE of 20.29% can be achieved in the P3CT-Na based inverted MAPbI3 solar cell. Abstract: The s-shaped J-V curve of perovskite solar cells can be eliminated using the solvent penetration (SP) process with a PCBM spacer. The experimental results show that the viscosity of the solvent used in the SP process influences the shunt and series resistances simultaneously. In addition, the fill factor of PEDOT:PSS based perovskite solar cells can be largely increased from 40.3% to 70.7% when the bathocuproine (BCP) molecules are dissolved in IPA solvent during the SP process, which significantly increases the power conversion efficiency (PCE) by 98.9%. Besides, the PCE of perovskite solar cells increases from 13.56% to 20.29% when the PEDOT:PSS film is replaced by a P3CT-Na thin film. It is noted that the absorbance spectra, photoluminescence (PL) spectra, time-resolved PL, Raman spectra and X-ray diffraction patterns demonstrate that the BCP molecules penetrate into the PCBM thin film and the PCBM/perovskite interface during the SP process, which increases the electron mobility of the PCBM thin film and passivates the interfacial MA cations in perovskite thin film, respectively. In other words, the solution-processed BCP small molecules are vertically distributed across the PCBM thin film. Our results help completely understand the entire roles of the solution-processed BCP molecules in the high-performance inverted-type perovskite solar cells.